The Role of Immunometabolism in the Pathogenesis of Systemic Lupus Erythematosus - Robinson, George Anthony; Wilkinson, Meredyth G. Ll.; Wincup, Chris (Frontiers in Immunology, 2022)
Systemic lupus erythematosus (SLE) is a chronic autoimmune disorder in which pathogenic abnormalities within both the innate and adaptive immune response have been described. In order to activated, proliferate and maintain this immunological response a drastic upregulation in energy metabolism is required. Recently, a greater understanding of these changes in cellular bioenergetics have provided new insight into the links between immune response and the pathogenesis of a number of diseases, ranging from cancer to diabetes and multiple sclerosis. In this review, we highlight the latest understanding of the role of immunometabolism in SLE with particular focus on the role of abnormal mitochondrial function, lipid metabolism, and mTOR signaling in the immunological phenomenon observed in the SLE. We also consider what implications this has for future therapeutic options in the management of the disease in future.